Attribution Effects of Time Pressure in Retail Supply Chain Relationships: Moving From "What" to "Why". Issue 3 (11th August 2014) - Thomas, Rodney W.; Davis‐Sramek, Beth; Esper, Terry L.; Murfield, Monique L.
<x xml:space="preserve">Abstract</x> Retail supply chains must be responsive to consumer demand and flexible in adapting to changing consumer preferences. As a result, suppliers are often expected to deal with time pressure demands from retailers. While previous research demonstrates that time pressure can have longer term relational costs that reduce collaborative behaviors and overall relationship quality, this mixed‐methods study goes further by accounting for attribution effects to explain why the time pressure occurs. Specifically, supplier perceptions for the reason of time pressure being within or beyond a retailer's control, rather than time pressure itself, appear to have a stronger effect on relational outcomes. By investigating time pressure through the lens of attribution theory, this research opens a new inquiry of research that moves away from examination of outcomes themselves (the "what"), to examining "why" the outcome occurred.